Gender Analysis on Productive Economy Program for Returnee Women Migrant Workers: A Case Study in Kenanga Village, Indramayu District - Pratiwi, Andi Misbahul; Wangka, Yusmiati Vistamika; Faizah, Andi Nur (Yayasan Jurnal Perempuan, 2020)
Indonesia is one of the countries of origin for migrant workers in the world. In the context of migration, the discourse on natural resources, sustainable economy, and women’s impowerment are not the mainstream discussion. The resilience or economic sustainability of returnee women migrant workers (RWMWs) is also a major problem in migration policy schemes and practices inIndonesia. This paper explores how the model of economic empowerment in Kenanga Village, Indramayu District, as a local initiative can bring welfare toward RWMWs and goes beyond the discourse of safe migration. The data in this research analyzed using Harvard and Longwee’ gender analysis tools as well as indicator of gender mainstreaming, and Naila Kabeer’s theory of empowerment. This paper finds that local initiatives of productive economy have a positive impact on the economic sustainability of RWMWs in Kenanga Village. It is important to develop economic resilience as an alternative to alleviate poverty. However, in the empowerment program,it is important to consider various aspects of gender justice.